Needs, service-costs and outcomes in foster care in three Ontario children's aid societies - MacDonald, Joan Matilda (University of Ottawa (Canada), 2006)
Costing studies are necessary to ensure that scarce funds are allocated to services that best meet children's needs and lead to positive changes in their functioning. The Production of Welfare (POW) model for costing social services provides a conceptual framework for examining variations in cost in relation to needs and outcomes. The few studies that have looked at costs of services to children and youth suggest that health needs, emotional/behavioural problems, gender and age may influence cost. Our study questions were: (1) What are the average annual per-child costs of foster care? (2) Do higher health needs predict higher costs? (3) Do higher costs during a 12-month period predict better outcomes? The outcomes included in the study were self-esteem, prosocial behaviour, emotional distress/anxiety, conduct disorder/physical aggression, indirect aggression and ill-health. The total average annual opportunity cost per child was $22,892 (N=119). Greater ill-health at baseline predicted higher costs. Cost did not predict changes on self-esteem, prosocial behaviour and emotional distress/anxiety. Contrary to expectations, higher costs were associated with increases in conduct disorder/physical aggression, indirect aggression and ill-health over the 12 months of the study. Kinship care was less expensive than regular foster care, but the study included only 8 children in kinship care. Our results suggest that higher expenditures are targeted at children with greater health needs. Costs may not have yet been able to predict positive changes in outcomes because the time period of the study was for the interventions to have the impact on behaviour that would bring about positive changes. This means that further research with a longer follow-up period is required. A prospective cost study could provide a more complete description of the total costs required to support a child in foster care. Given the small number of participants in kinship care in our study, the relationship between kinship care and cost can only be viewed as exploratory. A larger sample of children in kinship care could provide more information on the costs of kinship care and the relationship between costs and outcomes in kinship care in comparison to regular foster care.
Keywords: Social Work.; Psychology, Clinical.; Sociology, Public and Social Welfare.